2018
DOI: 10.1016/j.actbio.2018.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembling diphenylalanine peptide nanotubes selectively eradicate bacterial biofilm infection

Abstract: We outline, for the first time, the antibiofilm activity of diphenylalanine (FF) peptide nanotubes. Biofilm bacteria exhibit high tolerance to antimicrobials 10-10,000 times that of free-flowing planktonic forms. Biofilm infections are difficult to treat using conventional antimicrobial agents, leading to a rise in antimicrobial resistance. We discovered nanotubes composed of NH-FF-COOH demonstrated potent activity against staphylococcal biofilms implicated in hospital infections, resulting in complete kill at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
75
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 51 publications
1
75
1
Order By: Relevance
“…Reches and Gazit reported the ability of diphenylalanine peptide to form well‐ordered nanotubes from aqueous solutions, and their application as molds for metal nanowires . From there, the scientific interest related to this peptide grew exponentially; indeed, recent research works showed the use of diphenylalanine for antibacterial agents, piezoelectric components for energy harvesters, optical waveguides, hydrogels, drug delivery systems, and integration of metal nanocomposites . Taking this aromatic dipeptide as elementary motif, many chemical modifications were investigated to control the morphology of the self‐assembled nano‐objects, tailoring the system for the desired application .…”
Section: Introductionmentioning
confidence: 99%
“…Reches and Gazit reported the ability of diphenylalanine peptide to form well‐ordered nanotubes from aqueous solutions, and their application as molds for metal nanowires . From there, the scientific interest related to this peptide grew exponentially; indeed, recent research works showed the use of diphenylalanine for antibacterial agents, piezoelectric components for energy harvesters, optical waveguides, hydrogels, drug delivery systems, and integration of metal nanocomposites . Taking this aromatic dipeptide as elementary motif, many chemical modifications were investigated to control the morphology of the self‐assembled nano‐objects, tailoring the system for the desired application .…”
Section: Introductionmentioning
confidence: 99%
“…Molecular self-assembly has attracted extensive interest in the construction of antimicrobial and antifouling agents [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Self-assembly is a spontaneous process in which the molecular organization of diverse building blocks, including nucleic acids, peptides, proteins and lipids, organize into well-ordered structures at the nano-scale [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanism of this activity involves invasion into the bacterial cell followed by a reduction of glutathione levels [ 76 ]. The antibacterial properties of nano-assemblies formed by diphenylalanine have also been studied recently [ 19 , 20 ]. These assemblies cause membrane disruption in an E. coli model [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Large numbers of peptide gels have been reported for the functions of tissue engineering, nanoreactors, drug delivery vehicle, antibacterial agent and regenerative medicine . Phenylalanine‐phenylalanine (FF) dipeptide is usually used as the core recognition of the β‐amyloid fiber and may be the simplest peptide with kinds of self‐assembled structures driven by the π‐π stacking interaction between the benzene rings . However, most of the peptides consisting of FF can hardly dissolve in water.…”
Section: Introductionmentioning
confidence: 99%